2017
DOI: 10.1002/ccd.26921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic kidney disease on 2‐year clinical outcomes in patients treated with 6‐month or 24‐month DAPT duration: An analysis from the PRODIGY trial

Abstract: Moderate-to-severe CKD did not modify the effect of a prolonged or shortened DAPT duration in largely unselected patients undergoing stent implantation. Our analysis suggests that CKD should not be a major driver in the decision-making on the duration of DAPT after stent implantation. This exploratory study is underpowered and should be considered hypothesis-generating only. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…In contrast, in a study of previously revascularized patients with CAD, CKD defined as GFR<60 was associated with an adjusted HR for stroke of 2.3 (95% CI 1.2-4.7) 48 and our results could be explained by the limited power to detect differences between the groups. But it could also indicate that RD is not a strong risk factor for stroke in the present population, which is also a finding supported in a recent substudy of PROlonging Dual Antiplatelet Treatment After Grading stent-induced Intimal hyperplasia study (PRODIGY) where no difference in the risk of stroke or transient ischemic attack was observed between those with and without RD at 2-years of follow-up (HR 1.97, 95% CI (0.79-4.92) 136 .…”
Section: Influence Of Rd On Cvd Outcomes In Patients With Stable Cadsupporting
confidence: 87%
“…In contrast, in a study of previously revascularized patients with CAD, CKD defined as GFR<60 was associated with an adjusted HR for stroke of 2.3 (95% CI 1.2-4.7) 48 and our results could be explained by the limited power to detect differences between the groups. But it could also indicate that RD is not a strong risk factor for stroke in the present population, which is also a finding supported in a recent substudy of PROlonging Dual Antiplatelet Treatment After Grading stent-induced Intimal hyperplasia study (PRODIGY) where no difference in the risk of stroke or transient ischemic attack was observed between those with and without RD at 2-years of follow-up (HR 1.97, 95% CI (0.79-4.92) 136 .…”
Section: Influence Of Rd On Cvd Outcomes In Patients With Stable Cadsupporting
confidence: 87%
“…In a recent publication from the SWEDEHEART registry, Carrero et al demonstrated that prolonged, as compared to 3 months DAPT, was associated with lower risk of death, stroke, or reinfarction, regardless of underlying CKD . On the contrary, Valgimigli et al in a post‐hoc analysis of the PRODIGY trial, showed that prolonged DAPT did not reduce major adverse cardiovascular events, but this finding was again consistent between CKD and non‐CKD patients. While optimization of DAPT duration to harmonize thrombotic and bleeding risk in CKD patients is still a matter of controversy, the present meta‐analysis support, in indicated CKD PCI candidates, systematic use of newer generation DES.…”
Section: Discussionmentioning
confidence: 97%
“…Chronic kidney disease (CKD) is a prevalent risk factor for cardiovascular disease (CVD). Of note, CKD patients are more likely to die from CVD complications than to develop end‐stage kidney failure . In addition, CKD patients have increased risk of stent‐related complications when treated with percutaneous coronary interventions (PCI) such as stent thrombosis (ST) and target lesion/vessel revascularization (TLR/TVR).…”
Section: Introductionmentioning
confidence: 99%
“…Post hoc analyses of the Clopidogrel for the Reduction of Events During Observation (CREDO) and Prolonging Dual Antiplatelet Treatment After Grading Stent-Induced Intimal Hyperplasia Study (PRODIGY) trials performed in subjects with estimated glomerular filtration rate <60 mL/min/1.73 m 2 demonstrated that ≥1 year of DAPT did not affect the incidence of MACE [ 15 , 17 ]. However, DAPT for 1 year was compared with 1 month in the CREDO trial, which is not compatible with current guidelines.…”
Section: Discussionmentioning
confidence: 99%